FEATURES OF THE COURSE OF PREGNANCY IN WOMEN WITH FETOPLACENTAL INSUFFICIENCY - Yakubova, G.K.; Mirzaeva, D.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background. Fetoplacental insufficiency, a prevalent pregnancy complication, often results in fetal oxygen deprivation and stunted growth, ultimately contributing significantly to newborn health issues and fatalities. Purpose. The aim of this study is to examine the characteristics of pregnancy progression, as well as the maternal and fetal outcomes associated with placental insufficiency during pregnancy. Material and methods. A study was conducted involving 25 pregnant individuals diagnosed with placental insufficiency, focusing on a comprehensive analysis of their pregnancy progression. Results. The study found a significant number of perinatal complications among this group of women. A close relationship was established between the extent of placental insufficiency and the level of fetal oxygen deprivation (p<0,05), as well as a direct link between placental insufficiency and the worsening of fetal physical health issues (p<0,05). Conclusion. Women experiencing placental insufficiency are at an elevated risk of facing complications such as miscarriage, reduced fetal oxygen supply, impaired fetal growth, and adverse perinatal outcomes.